Community Structure and Ecological Roles of Soil Macrofauna in Sumatran Elephant Feces as an Effort to Conserve Soil Biodiversity in Bengkulu Elephant Training Center, Indonesia: Community Structure and Ecological Roles of Soil Macrofauna in Sumatran Elephant Feces - Darmi, Darmi; Rizwar, Rizwar; Warosuly, Tri Nurhidayati; Julita, Helika (Journal of Tropical Life Science, 2026)
Elephant feces are a source of organic material that has the potential to support soil ecosystem sustainability. Elephant feces serve as a microhabitat, providing nutrients and a place to live for soil macrofauna that plays an important role in soil decomposition. However, the understanding of the community structure and ecological contribution of macrofauna in elephant feces is still limited, especially in the Bengkulu Elephant Training Center area. The objective of this study was to analyze the community structure and ecological roles of soil macrofauna in Sumatran elephant feces at the Seblat Elephant Conservation Area. Soil macrofauna in elephant feces is divided into two groups, namely Macroarthropods and Oligochaeta (Megadrilli earthworms). Macroarthropod samples were collected using the handsorting method on each bolus of feces, while earthworms were collected using the square method and the handsorting method on feces that had undergone further decomposition. The community structure of soil macrofauna in elephant feces consists of 18 species. Arthropoda comprises 15 species belonging to the classes Hexapoda, Arachnida, Crustacea, and Diplopoda. Trigoniulus corallinus is a dominant macroarthropod species with an absolute category (very frequently found) and a wide distribution in elephant feces.  Oligochaeta consists of three species of megadrilli earthworms, namely Pontoscolex corethrurus, Drawida sp., and Pheretima  Javanica.  Drawida sp. have the highest density and were classified as constant (frequently found) in elephant feces. The Shannon-Wiener and Simpson’s diversity indices for soil macroarthropods are relatively high, whereas those for Oligochaeta are low. Based on ecological roles, soil macroarthropods consist of detritivores, omnivores, predators, and herbivores. Detritivores are dominant in elephant feces. Among the Oligochaeta, epigeic earthworms are more dominant than endogeic earthworms. The presence of elephant dung in the central area of the Elephant Training Center is a means of conserving soil biodiversity, thereby contributing to improving soil quality and fertility.